Comparison of high density and nitrogen seeded detachment using SOLPS-ITER simulations of the tokamak á configuration variable. (26th October 2020) - Smolders, A; Wensing, M; Carli, S; De Oliveira, H; Dekeyser, W; Duval, B P; Février, O; Gahle, D; Martinelli, L; Reimerdes, H; Theiler, C; Verhaegh, K; et al.
Abstract: First of a kind SOLPS-ITER simulations on tokamak á configuration variable (TCV) that include nitrogen have been performed to model recent nitrogen seeded detachment experiments. Based on spectroscopic measurements, a nitrogen recycling coefficient R p N ≈ 0.3–0.5 on the graphite walls of TCV is estimated. The experimentally observed decrease of core nitrogen density with increasing plasma density is reproduced and linked to a reduction of the ionisation mean free path in the scrape-off layer. Although the influence of sputtered carbon impurities from TCV's graphite wall cannot be fully eliminated, seeding nitrogen increases control over the total impurity density. This facilitates disentangling the effect of impurities from that of high upstream density on the main characteristics of detachment, namely target power and ion current reductions and the development of a parallel pressure drop. Increasing the density and the seeding rate reduce the power on the divertor targets in a different way: with density, the ion current increases and the target temperature strongly decreases, whereas seeding impurities decreases the ion current and affects less strongly the temperature. The reduction in ion current when seeding nitrogen is due to a lower ionisation source, which is not related to power limitation nor an increased momentum loss, but to a decrease of the ionisation reaction rate. Impurity seeding leads to less volumetric momentum losses (and hence pressure drop) than density ramps, for the same level of energy flux reduction. Additionally, main chamber sputtering of carbon is identified as a possible explanation for the missing target ion current roll-over during density ramps in the simulations.